DIMENSI MORAL DALAM PROSES PEMBANGUNANDAERAH: SEBUAH ANALISIS PEMBANGUNAN KAWASAN PERBATASAN NEGARA DI PROVINSI KALIMANTAN UTARA - Arry Bainus; Sonny Sudiar (Jurnal Administrative Reform, 2017)
One of the main challenges in describing and analyzing development process in border area is its complexity and scope. It requires the use of development concept and moral assessment, so those concept are discussed. This article is an analysis about the development process in the border area of north Kalimantan. Research shows that the real conditions in the border area of north Kalimantan are still poor. It was proven by lack of infrastructure, and the basic need services such as education and health. What does it take to enhance the quality of development? Does it require an ethic approach? Moral dimension is designed to help avoid such wrong model in development implementation and support for sustained improvement in the border area of north Kalimantan.